Exploring the Meaning of Tafaqquh Fiddin as Intellectual and Spiritual Jihad - Sunarya, Eva; Sassi, Komaruddin (ALSYS, 2025)
Tafaquh fiddin in Islamic scholarship emphasizes the importance of comprehensive understanding and deepening of religious knowledge. This study aims to explore the meaning of tafaquh fiddin through the lenses of intellectual and spiritual jihad and assess its relevance to contemporary Muslim life. Employing a qualitative methodology, the research utilizes a literature review encompassing Qur’anic verses, hadith, and classical and modern Islamic texts. The findings reveal that tafaquh fiddin extends beyond theoretical religious study to embody a form of jihad that integrates the expansion of Islamic insight with the practical implementation of religious values in daily life. The study concludes that tafaquh fiddin serves as a critical foundation for cultivating intellectually, morally, and spiritually resilient Muslims, thereby maintaining its significance in addressing contemporary challenges. Keywords: Tafaquh fiddin; Qur’an (Q.S. At-Taubah); Intellectual Jihad; Spiritual Jihad; Qur’anic Tafsir